Effect of the acetylation process on native starches of yam (Dioscorea spp.) (2016)
In Colombia, it is necessary to produce native and modified starches for the use of amylaceous raw materials of major socioeconomic importance. In this study, the effects of the acetylation process on structural, morphological and functional properties of native starches yam, Dioscorea spp. (D. alata and D. rotundata) were evaluated. Chemical modification by esterification with acetic anhydride was performed at different reaction times, and morphological and structural changes were assessed using the following techniques: infrared spectroscopy (FTIR), X-ray diffraction and scanning electron microscopy (SEM). Acetylation produced slight changes in the granule morphology, and a decreased degree of crystallinity (DC) associated with a slight increase in the amylose content was observed. The introduction of acetyl groups into the starch structure caused a decrease in the gelatinization temperature and an increased retro gradation tendency. The acetylated starches had low degrees of substitution (DS0.2), meaning they can be used in the food industry, considering that they showed greater stability, greater water absorption capacity and better solubility than native starches.